Open leadership : how social technology can transform the way you lead. - Li, Charlene, 1966- (San Francisco : Jossey-Bass, 2010)
An essential guide for leaders who want to use social media to be "open" while maintaining control "Be Open, Be Transparent, Be Authentic" are the current leadership mantras-but companies often push back. Business is premised on the concept of control and yet the new world order demands openness-leaders do not know how to be open and be in control. This must-have resource will help the modern leader understand how to lead in the new open world-where blogging, twittering, facebooking, and digging are becoming the norm. the author lays out the steps that leaders must take to transform their organizations and themselves into being "open" -and exactly what that will mean. > Shows how to use social media to become an open organization > Offers basic advice for leaders who are adapting to the new era of openness in the marketplace > The author Charlene Li is one of the foremost experts on social media and technologies In easy-to-understand language, this book will help leaders orient themselves to social networking and other technological advances.
Keywords: Leidinggeven; Sociale netwerken -- Internet